PEMBELAJARAN BAHASA DAERAH GORONTALO PADA ANAK USIA DINI - Wenny Hulukati; Maryam Rahim; Yusuf Djafar (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2017)
Local language is one of the characteristics as well as a cultural richness of an area that needs to be preserved existence. In Gorontalo, some teenagers are not confident in their local languages, and children who are unable to communicate with Gorontalo language even in very simple contexts, especially people in urban areas. Learning local languages of Gorontalo at the level of Early Childhood Education is considered to be one solution, considering the early age is a potential moment to develop various potentials, including the potential for language. Conditions encountered in early childhood education institutions show that learning / language activities in Gorontalo are not structured, resulting in the development of Gorontalo language ability in children is very low. For that reason, learning language of Gorontalo in early childhood needs to be organized in a systematic and structured based on clear guidelines. These guidelines include: (a) learning programs that are appropriate to the characteristics of early childhood development, (b) learning materials appropriate to the characteristics of early childhood development, and (c) evaluation guidelines that can clearly measure the development of local language skills in children aged early.